Chlamydia trachomatis Growth and Cytokine mRNA Response in a Prostate Cancer Cell Line - Ivan M. Petyaev; Naylia A. Zigangirova; Elena Y. Morgunova; Nigel H. Kyle; Elena D. Fedina; Yuriy K. Bashmakov (Advances in Urology)
In the present paper, we report that C. trachomatis can be efficiently propagated and affect mRNA expression for two major cytokines, relevant to tumor progression, in CWR-R1 cells, a malignant prostate cell line. CWR-R1 and McCoy cells, a classic cell line for chlamydial research, were grown and infected with C. trachomatis under similar conditions. Cell monolayers were harvested for RNA analysis and immunostaining with major outer membrane protein (MOMP) antibody at 24, 48, and 72 hours of the postinfection (hpi) period. It was shown that the infectious cycle of chlamydial pathogen in CWR-R1 cells resembles the progression of C. trachomatis infection in McCoy cells but with a few important differences. First of all, the initial stage of C. trachomatis propagation in CWR-R1 cells (24 hpi) was characterized by larger inclusion bodies and more intense, specific immunofluorescent staining of infected cells as compared with McCoy cells. Moreover, there was a corresponding increase in infective progeny formation in CWR-R1 cells along with mRNA for EUO, a crucial gene controlling the early phase of the chlamydial development cycle (24 hpi). These changes were more minimal and became statistically insignificant at a later time point in the infectious cycle (48 hpi). Altogether, these data suggest that the early phase of C. trachomatis infection in CWR-R1 cells is accompanied by more efficient propagation of the pathogen as compared with the growth of C. trachomatis in McCoy cells. Furthermore, propagation of C. trachomatis in CWR-R1 cells leads to enhanced transcription of interleukin-6 and fibroblast growth factor-2, genes encoding two important proinflammatory cytokines implicated in the molecular mechanisms of chemoresistance of prostate cancer and its ability to metastasize. The possible roles of reactive oxygen species and impaired mitochondrial oxidation in the prostate cancer cell line are discussed as factors promoting the early stages of C. trachomatis growth in CWR-R1 cells.